High-strength polypropylene hollow plastic plate and preparation method thereof
Polymerization is solved by using interpenetrating network of branched epoxy resin and bisphenol A-type epoxy resin in polypropylene hollow plastic boards and the composite process of maleic anhydride grafting polypropylene, calcium carbonate, talc powder and glass fibers in polypropylene hollow plastic boards The shortcomings of acrylic plates in terms of mechanical properties and heat resistance have significantly improved their mechanical properties and UV resistance.
Patent Information
- Application Number
- CN202411460145.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The existing polypropylene hollow sandwich plates have shortcomings in terms of mechanical properties, heat resistance and ultraviolet resistance, and are difficult to meet the needs of higher strength and weather resistance.
The branched epoxy resin is combined with bisphenol A type epoxy resin, and an interpenetrating network is formed in the material system of polypropylene hollow plastic board, combined with maleic anhydride grafted polypropylene, calcium carbonate, talc powder and glass fiber. Composite process improves the mechanical properties and heat resistance of polypropylene plates.
The mechanical properties, heat resistance and UV resistance of polypropylene hollow plastic sheets are significantly improved, and their flat compressive strength, bending strength and UV retention rate are enhanced.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polypropylene composite boards, in particular to a high-strength polypropylene hollow plastic board and a preparation method thereof. Background Art
[0002] With the increasing demand for lightweight panels, sandwich panels are widely used in pressure-bearing components such as logistics and transportation, vehicle traffic, civil engineering, and electrical equipment. Their structure, achieved by laminating face sheets on either side of a lightweight, thick core, offers low weight yet high rigidity and strength. Common materials include polypropylene, which is melted at high temperatures in an extruder and then extruded into sheets. The core material can be the same as the face sheets, making them more easily and quickly recyclable. To address the demand for higher strength in sandwich panels, we propose a high-strength polypropylene hollow plastic sheet and its preparation method. Summary of the Invention
[0003] The object of the present invention is to provide a high-strength polypropylene hollow plastic plate and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0004] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a high-strength polypropylene hollow plastic plate, comprising the following processes:
[0005] Polypropylene, maleic anhydride grafted polypropylene, filler, epoxy resin, curing agent and additives are mixed, extruded, pulled and formed into panels and core layers respectively; the panel and core layer are compounded to obtain a polypropylene hollow plastic board.
[0006] Furthermore, the polypropylene hollow plastic plate includes 2 to 3 groups of face panels, and a core layer is provided between two adjacent groups of face panels.
[0007] Furthermore, the cross-sectional structure of the core layer is square, circular, crisscross or honeycomb.
[0008] Furthermore, the thickness of the polypropylene hollow plastic plate is 4 to 15 mm;
[0009] The thickness of the panel is 1 to 5 mm, and the thickness of the core layer is 2 to 10 mm.
[0010] In the above technical solution, a polypropylene hollow plastic sheet (hereinafter referred to as a polypropylene sheet) is formed by combining two to three face sheets and one to two core layers. From top to bottom, the polypropylene sheet comprises the following structure: face sheet, core layer, face sheet; or face sheet, core layer, face sheet, core layer, face sheet. The core layer is a hollow structure, and the cross-sectional or longitudinal structure of the hollow structure can be square, circular, crisscross, or honeycomb, enabling the resulting polypropylene sheet to achieve excellent mechanical properties.
[0011] Furthermore, in the polypropylene hollow plastic plate, the panel and the core layer are made of the same material;
[0012] The amount of each component is, by mass: 85-100 parts of polypropylene, 10-15 parts of maleic anhydride grafted polypropylene, 20-30 parts of filler, 5-25 parts of epoxy resin, 0.1-5.0 parts of curing agent, and 1.0-2.0 parts of auxiliary agent.
[0013] Furthermore, the filler includes 6 to 8 parts of talc, 10 to 15 parts of calcium carbonate, and 4 to 7 parts of glass fiber;
[0014] The auxiliary agent includes 0.5 to 1.0 parts of coupling agent and 0.5 to 1.0 parts of antioxidant;
[0015] The epoxy resin is a mixture of one or more of branched epoxy resin, bisphenol A epoxy resin, bisphenol F epoxy resin and novolac epoxy resin.
[0016] Polypropylene: Dongming 500N and Jiutai L5E89, sourced from Suqian Qinfa Plastic Products Technology Co., Ltd.
[0017] Maleic anhydride grafted polypropylene: PO 1020, from ExxonMobil Chemical Company;
[0018] Calcium carbonate: average particle size 40-50 nm, sourced from Shanxi Xintai Hengxin Nanomaterials Co., Ltd.
[0019] Talc: HAR T84, sourced from Yiruishi (Shanghai) Investment Management Co., Ltd.
[0020] Glass fiber: 3-6mm in length, SiO2 content >95.0%, sourced from Changzhou Qiushuo Chemicals Co., Ltd.
[0021] The coupling agent is one of KH-560, KH-550, and KH-570;
[0022] The antioxidants are antioxidant 1010 and antioxidant 168, with a mass ratio of 2:1.
[0023] In the above technical solution, polypropylene is used as the main resin and calcium carbonate is used as nanoparticles. Its filling can promote polypropylene nucleation, improve the crystallinity of polypropylene, and contribute to the improvement of the strength of the composite material. Talc is in flaky form and works in conjunction with calcium carbonate as a filler for polypropylene, effectively reinforcing the polypropylene composite material. The addition of glass fiber, compounded with calcium carbonate and talc, can further improve the strength of polypropylene. A coupling agent is added to the polypropylene board material system to modify the surface of the fillers calcium carbonate, talc, and glass fiber, making them more dispersible in polypropylene and fully realizing the material properties. Maleic anhydride grafted polypropylene can also effectively improve the affinity between the filler and polypropylene and the dispersion of the filler, thereby improving the mechanical properties of the polypropylene board.
[0024] The use of epoxy resin and its curing agent allows it to solidify during the coextrusion process and disperse under high shear forces, forming tiny particles that are distributed throughout the polypropylene system. This effectively improves the rigidity and modulus of the polypropylene sheet, resulting in enhanced mechanical properties. The maleic anhydride-grafted polypropylene component of the polypropylene sheet material system has an anhydride group that reacts with the epoxy resin. Furthermore, the epoxy resin includes a branched epoxy resin with an epoxy functionality greater than 2, which forms an interpenetrating network with the polypropylene molecular chains during coextrusion. This increases the entanglement and crosslinking between the system's molecules, enhancing melt strength and improving the mechanical properties, heat resistance, and UV resistance of the resulting polypropylene hollow plastic sheet.
[0025] Further, the branched epoxy resin is prepared by the following process:
[0026] Under nitrogen atmosphere, benzophenone diol, bismaleimide glycidyl ether and tetrabutylammonium bromide were mixed, stirred and heated to 80-90°C, and kept warm for reaction for 24 hours; cooled to room temperature, tetrahydrofuran was added to dissolve, deionized water was added to separate the layers, rotary evaporated, and vacuum dried to obtain a branched epoxy resin.
[0027] Furthermore, the branched epoxy resin is prepared from the following components by weight: 10 parts of benzophenone diol, 54 to 61 parts of bismaleimide glycidyl ether, and 0.8 to 1.0 parts of tetrabutylammonium bromide.
[0028] Further, benzophenone diol is prepared by the following process:
[0029] Mix 2,4-dihydroxybenzophenone and sodium hydroxide aqueous solution, stir and dissolve, add epichlorohydrin under nitrogen atmosphere, heat to 90-95°C and react for 3-4 hours; wash with water at 80±2°C, take the organic phase, dry it, filter it, distill it under reduced pressure, recrystallize it with ethanol, and dry it in vacuum to obtain epoxybenzophenone;
[0030] Mix epoxy benzophenone and potassium hydroxide aqueous solution, heat to 80-85°C, and react for 9-10 hours; add dichloromethane, separate the liquids, take the organic phase, wash with water, dry, distill under reduced pressure, and dry in vacuum to obtain benzophenone diol.
[0031] Furthermore, the molar ratio of 2,4-dihydroxybenzophenone to epichlorohydrin is 1:(2.5-3.2);
[0032] The ratio of 2,4-dihydroxybenzophenone and sodium hydroxide aqueous solution is 0.2 mol / 100 mL;
[0033] The concentration of the sodium hydroxide aqueous solution was 2M.
[0034] Furthermore, the ratio of epoxybenzophenone to potassium hydroxide aqueous solution is 30 g / 10 mL;
[0035] The concentration of the potassium hydroxide aqueous solution was 30 wt%.
[0036] Further, bismaleimide glycidyl ether is prepared by the following process:
[0037] Mix bismaleimide, trimethylolpropane tris(3-mercaptopropionate) and a catalyst in chloroform, heat to 58-62°C under nitrogen atmosphere, and stir to react for 100-150 minutes; distill under reduced pressure, wash, and dry to obtain bismaleimide mercaptopropionate;
[0038] Maleimide mercaptopropionate, allyl glycidyl ether and a photoinitiator are mixed in chloroform and subjected to ultraviolet irradiation for reaction for 4 to 5 hours; the mixture is distilled under reduced pressure, washed and dried to obtain bismaleimide glycidyl ether.
[0039] Furthermore, the molar ratio of bismaleimide, trimethylolpropane tris(3-mercaptopropionate), and catalyst triethylamine is 1:(2.2-2.5):(0.05-0.10);
[0040] The ratio of maleimide to chloroform was 30 g / 100 mL.
[0041] Furthermore, the molar ratio of maleimide mercaptopropionate to allyl glycidyl ether is 1:(4.0-4.2);
[0042] The photoinitiator is photoinitiator 184, and the amount used is 1% to 5% of the total mass of maleimide mercaptopropionate and allyl glycidyl ether;
[0043] The ratio of maleimidomercaptopropionate to chloroform was 15 g / 100 mL.
[0044] Furthermore, the bismaleimide is one of N,N'-cyclohexanebismaleimide, disulfide-bismaleimidoethane, 1,10-bis(maleimido)decane, 1,8-bis(maleimido)diethylene glycol, 1,11-bis(maleimido)triethylene glycol, 1,23-bis(maleimido)heptanediol, bismaleimide-diethylene glycol, N,N'-tetramethylenebismaleimide, and N,N'-(4,4'-methylenediphenyl)bismaleimide 358.
[0045] In the above technical solution, bismaleimide is mixed with trimethylolpropane tris(3-mercaptopropionate). Under the action of heat, the double bond in bismaleimide reacts with the thiol group in trimethylolpropane tris(3-mercaptopropionate) to produce a click reaction, so that the prepared bismaleimide mercaptopropionate has a multi-thiol structure; it is then reacted with the allyl group in allyl glycidyl ether to introduce multiple epoxy groups at the end group of the bismaleimide compound. By controlling the amount of substance, the prepared bismaleimide glycidyl ether contains four groups of epoxy groups. 2,4-dihydroxybenzophenone is mixed with epichlorohydrin. Under the action of alkali, the 4-hydroxy structure in 2,4-dihydroxybenzophenone reacts with the chlorine group in epichlorohydrin to obtain epoxybenzophenone; then, under the action of alkali solution, the epoxy group is ring-opened to form two hydroxyl groups, thereby obtaining benzophenone diol.
[0046] Under the action of tetrabutylammonium bromide, an epoxy compound containing bismaleimide (bismaleimide glycidyl ether) and a diol containing a benzophenone group (benzophenone diol) are mixed to allow ring opening and hydroxyl reaction to prepare a branched epoxy resin. The maleimide functional group introduced into the branched epoxy resin can effectively improve the mechanical properties and heat resistance of the epoxy resin cured product and the polypropylene board prepared therefrom. The introduction of the benzophenone group can improve the sensitivity of the polypropylene board to ultraviolet light and improve its weather resistance; it can also inhibit the ring opening of the maleimide structure, allowing it to maintain its reinforcing properties, thereby enabling the prepared polypropylene board to obtain higher mechanical properties and thermal stability; the interfacial properties of the epoxy resin cured product with glass fiber and polypropylene board can also be effectively enhanced.
[0047] Furthermore, the mixing process conditions are: temperature 100-120°C, time 20-30 min;
[0048] The extrusion process conditions are: temperature 190-210°C, screw speed 180-200 rpm;
[0049] The composite process conditions are: temperature 190-200°C, pressure 0.25-2.5MPa.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] 1. The present invention describes a high-strength polypropylene hollow plastic sheet and its preparation method. The polypropylene hollow plastic sheet is constructed by combining a face plate with a core layer having a hollow structure, achieving excellent mechanical properties. A branched epoxy resin and a bisphenol A epoxy resin are compounded and added to the material system of the polypropylene hollow plastic sheet to form an interpenetrating network. This increases the entanglement and crosslinking between molecules in the system, enhancing melt strength and improving the mechanical properties, heat resistance, and UV resistance of the resulting polypropylene hollow plastic sheet.
[0052] 2. The present invention describes a high-strength polypropylene hollow plastic plate and a preparation method thereof, which is prepared by reacting bismaleimide glycidyl ether and benzophenone diol through a branched epoxy resin. The introduced maleimide and benzophenone groups enable the polypropylene hollow plastic plate to obtain higher mechanical properties, reduce sensitivity to ultraviolet light, and improve weather resistance and heat resistance. DETAILED DESCRIPTION
[0053] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0054] In the following specific embodiments,
[0055] Polypropylene: Dongming 500N and Jiutai L5E89, sourced from Suqian Qinfa Plastic Products Technology Co., Ltd.
[0056] Maleic anhydride grafted polypropylene: PO 1020, from ExxonMobil Chemical Company;
[0057] Calcium carbonate: average particle size 40-50 nm, sourced from Shanxi Xintai Hengxin Nanomaterials Co., Ltd.
[0058] Talc: HAR T84, sourced from Yiruishi (Shanghai) Investment Management Co., Ltd.
[0059] Glass fiber: 3-6mm in length, SiO2 content >95.0%, sourced from Changzhou Qiushuo Chemicals Co., Ltd.
[0060] The coupling agent is KH-550; the antioxidants are antioxidant 1010 and antioxidant 168, with a mass ratio of 2:1;
[0061] The phenolic epoxy resin is o-cresol epoxy resin, brand NPCN-704, NPCN-638, with a mass ratio of 9:1, sourced from Guangzhou Yezeng Chemical Co., Ltd.
[0062] The curing agent is dicyandiamide (DICY-P), which is sourced from Gaide Chemical;
[0063] The accelerator is 2-ethyl-4-methylimidazole (2E4MZ), which is from Gaide Chemical;
[0064] The polypropylene hollow plastic sheet includes two sets of face plates and one core layer. The thickness of the polypropylene hollow plastic sheet is 10 mm. The thickness of the face plates is 3 mm. The thickness of the core layer is 7 mm. The cross-section structure is a hollow circle with a diameter of 8 mm and a wall thickness of 0.32 mm. It is formed by extrusion rollers.
[0065] The "parts" mentioned below are all parts by mass.
[0066] Example 1: A method for preparing a high-strength polypropylene hollow plastic plate, comprising the following steps:
[0067] Step (1), 1.1. Take 2,4-dihydroxybenzophenone and 2M sodium hydroxide aqueous solution, mix, stir and dissolve, under nitrogen atmosphere, add epichlorohydrin, heat to 90 ° C and react for 4h; wash with water at 80 ° C, take the organic phase and dry it, filter, distill under reduced pressure, recrystallize from ethanol, and dry in vacuo to obtain epoxybenzophenone; the molar ratio of 2,4-dihydroxybenzophenone and epichlorohydrin is 1:2.5; the ratio of 2,4-dihydroxybenzophenone and sodium hydroxide aqueous solution is 0.2 mol / 100 mL;
[0068] Mix epoxy benzophenone and 30 wt% potassium hydroxide aqueous solution, heat to 80°C, and react for 10 hours; add dichloromethane, separate the liquids, take the organic phase, wash with water, dry, distill under reduced pressure, and dry in vacuum to obtain benzophenone diol; the ratio of epoxy benzophenone to potassium hydroxide aqueous solution is 30 g / 10 mL;
[0069] 1.2. Mix 30 g of N,N'-tetramethylenebismaleimide, trimethylolpropane tris(3-mercaptopropionate), and the catalyst in 100 mL of chloroform. Under a nitrogen atmosphere, heat to 58°C and stir for 150 min. Distill under reduced pressure, wash, and dry to obtain bismaleimide mercaptopropionate.
[0070] Mix 30 g of maleimide mercaptopropionate, allyl glycidyl ether, and 1% photoinitiator 184 in 200 mL of chloroform and irradiate with ultraviolet light for 4 h; distill under reduced pressure, wash, and dry to obtain bismaleimide glycidyl ether;
[0071] The molar ratio of N,N'-tetramethylenebismaleimide, trimethylolpropane tris(3-mercaptopropionate), and catalyst triethylamine is 1:2.2:0.05; the mass ratio of maleimide mercaptopropionate and allyl glycidyl ether is 10:4.4;
[0072] 1.3. Under a nitrogen atmosphere, mix 10 parts of benzophenone diol, 54 parts of bismaleimide glycidyl ether, and 0.8 parts of tetrabutylammonium bromide, stir, and heat to 80°C for 24 hours. Cool to room temperature, dissolve in tetrahydrofuran, add deionized water, separate the layers, rotary evaporate, and vacuum dry to obtain a branched epoxy resin.
[0073] Step (2), 100 parts of polypropylene, 10 parts of maleic anhydride grafted polypropylene, 6 parts of talc, 10 parts of calcium carbonate, 4 parts of glass fiber, 0.5 parts of coupling agent, 5 parts of epoxy resin (the mass ratio of bisphenol A epoxy resin and branched epoxy resin is 2:1), 0.1 parts of curing agent and 0.5 parts of antioxidant are mixed (temperature 100°C, time 30min), extruded (temperature 190°C, screw speed 180rpm), pulled and stretched to form a panel and a core layer, respectively, and compounded (temperature 190°C, pressure 0.35MPa) to obtain a polypropylene hollow plastic plate.
[0074] Example 2: A method for preparing a high-strength polypropylene hollow plastic plate, comprising the following steps:
[0075] Step (1), 1.1. Take 2,4-dihydroxybenzophenone and 2M sodium hydroxide aqueous solution, mix, stir and dissolve, under nitrogen atmosphere, add epichlorohydrin, heat to 92 ° C and react for 3.5h; wash with water at 80 ° C, take the organic phase and dry it, filter, distill under reduced pressure, recrystallize from ethanol, and dry in vacuo to obtain epoxybenzophenone; the molar ratio of 2,4-dihydroxybenzophenone and epichlorohydrin is 1:2.9; the ratio of 2,4-dihydroxybenzophenone and sodium hydroxide aqueous solution is 0.2mol / 100mL;
[0076] Mix epoxy benzophenone and 30 wt% potassium hydroxide aqueous solution, heat to 82°C, and react for 9.5 hours; add dichloromethane, separate the liquids, take the organic phase, wash with water, dry, distill under reduced pressure, and dry in vacuum to obtain benzophenone diol; the ratio of epoxy benzophenone to potassium hydroxide aqueous solution is 30 g / 10 mL;
[0077] 1.2. Combine 30 g of 1,11-bis(maleimido)triethylene glycol, trimethylolpropane tris(3-mercaptopropionate), and the catalyst in 100 mL of chloroform. Under a nitrogen atmosphere, heat to 60°C and stir for 120 min. Distill under reduced pressure, wash, and dry to obtain bismaleimidomercaptopropionate.
[0078] Mix 30 g of maleimide mercaptopropionate, allyl glycidyl ether, and 3% of photoinitiator 184 in 200 mL of chloroform and irradiate with ultraviolet light for 4.5 h; distill under reduced pressure, wash, and dry to obtain bismaleimide glycidyl ether;
[0079] The molar ratio of 1,11-bis(maleimido)triethylene glycol, trimethylolpropane tris(3-mercaptopropionate), and catalyst triethylamine is 1:2.4:0.08; the mass ratio of maleimidomercaptopropionate and allyl glycidyl ether is 10:4.1;
[0080] 1.3. Under a nitrogen atmosphere, mix 10 parts of benzophenone diol, 58 parts of bismaleimide glycidyl ether, and 0.9 parts of tetrabutylammonium bromide, stir, and heat to 85°C for 24 hours. Cool to room temperature, dissolve in tetrahydrofuran, add deionized water, separate the layers, rotary evaporate, and vacuum dry to obtain a branched epoxy resin.
[0081] Step (2), 93 parts of polypropylene with 12 parts of maleic anhydride grafted polypropylene, 7 parts of talc, 12 parts of calcium carbonate, 5 parts of glass fiber, 0.8 parts of coupling agent, 15 parts of epoxy resin (the mass ratio of bisphenol A epoxy resin and branched epoxy resin is 1:1), 2.5 parts of curing agent and 0.8 parts of antioxidant are mixed (temperature 110°C, time 25min), extruded (temperature 200°C, screw speed 190rpm), pulled and stretched to form a panel and a core layer, respectively, and compounded (195°C, pressure 0.30MPa) to obtain a polypropylene hollow plastic plate.
[0082] Example 3: A method for preparing a high-strength polypropylene hollow plastic plate, comprising the following steps:
[0083] Step (1), 1.1. Take 2,4-dihydroxybenzophenone and 2M sodium hydroxide aqueous solution, mix, stir and dissolve, add epichlorohydrin under nitrogen atmosphere, heat to 95 ° C and react for 3h; wash with water at 80 ° C, take the organic phase and dry it, filter, distill under reduced pressure, recrystallize from ethanol, and dry in vacuo to obtain epoxybenzophenone; the molar ratio of 2,4-dihydroxybenzophenone to epichlorohydrin is 1:3.2; the ratio of 2,4-dihydroxybenzophenone to sodium hydroxide aqueous solution is 0.2 mol / 100 mL;
[0084] Mix epoxy benzophenone and 30 wt% potassium hydroxide aqueous solution, heat to 85°C, and react for 9 hours; add dichloromethane, separate the liquids, take the organic phase, wash with water, dry, distill under reduced pressure, and dry in vacuum to obtain benzophenone diol; the ratio of epoxy benzophenone to potassium hydroxide aqueous solution is 30 g / 10 mL;
[0085] 1.2. Mix 30 g of bismaleimide-diethylene glycol, trimethylolpropane tris(3-mercaptopropionate), and the catalyst in 100 mL of chloroform. Under a nitrogen atmosphere, heat to 62°C and stir for 100 min. Distill under reduced pressure, wash, and dry to obtain bismaleimide mercaptopropionate.
[0086] Mix 30 g of maleimide mercaptopropionate, allyl glycidyl ether, and 5% photoinitiator 184 in 200 mL of chloroform and irradiate with ultraviolet light for 5 h; distill under reduced pressure, wash, and dry to obtain bismaleimide glycidyl ether;
[0087] The molar ratio of bismaleimide-diethylene glycol, trimethylolpropane tris(3-mercaptopropionate), and catalyst triethylamine is 1:2.5:0.10; the molar ratio of maleimide mercaptopropionate and allyl glycidyl ether is 10:3.8;
[0088] 1.3. Under a nitrogen atmosphere, mix 10 parts of benzophenone diol, 61 parts of bismaleimide glycidyl ether, and 1 part of tetrabutylammonium bromide, stir, and heat to 90°C for 24 hours. Cool to room temperature, dissolve in tetrahydrofuran, add deionized water, separate the layers, rotary evaporate, and vacuum dry to obtain a branched epoxy resin.
[0089] Step (2), 85 parts of polypropylene with 15 parts of maleic anhydride grafted polypropylene, 8 parts of talc, 15 parts of calcium carbonate, 7 parts of glass fiber, 1.0 part of a coupling agent, 25 parts of an epoxy resin (the mass ratio of bisphenol A epoxy resin to branched epoxy resin is 1:2), 5.0 parts of a curing agent and 1.0 part of an antioxidant are mixed (temperature 120°C, time 20 min), extruded (temperature 210°C, screw speed 200 rpm), pulled and stretched to form a panel and a core layer, respectively, and compounded (temperature 200°C, pressure 0.27 MPa) to obtain a polypropylene hollow plastic plate.
[0090] Comparative Example 1: A method for preparing a high-strength polypropylene hollow plastic plate, comprising the following processes:
[0091] Step (1), 30g of N,N'-tetramethylenebismaleimide, trimethylolpropane tris(3-mercaptopropionate), and a catalyst were mixed in 100mL of chloroform, heated to 58°C under a nitrogen atmosphere, and stirred for reaction for 150min; vacuum distillation, washing, and drying to obtain bismaleimide mercaptopropionate;
[0092] Mix 30 g of maleimide mercaptopropionate, allyl glycidyl ether, and 1% photoinitiator 184 in 200 mL of chloroform and irradiate with ultraviolet light for 4 h; distill under reduced pressure, wash, and dry to obtain bismaleimide glycidyl ether;
[0093] The molar ratio of N,N'-tetramethylenebismaleimide, trimethylolpropane tris(3-mercaptopropionate), and catalyst triethylamine is 1:2.2:0.05; the mass ratio of maleimide mercaptopropionate and allyl glycidyl ether is 10:4.4;
[0094] Under nitrogen atmosphere, 4.2 parts of 1,5-pentanediol, 54 parts of bismaleimide glycidyl ether, and 0.8 parts of tetrabutylammonium bromide were mixed, stirred, and heated to 80°C for 24 hours. The mixture was cooled to room temperature, tetrahydrofuran was added to dissolve the mixture, deionized water was added to separate the layers, rotary evaporated, and vacuum dried to obtain a branched epoxy resin.
[0095] Step (2) is the same as in Example 1 to obtain a polypropylene hollow plastic plate.
[0096] Comparative Example 2: A method for preparing a high-strength polypropylene hollow plastic plate, comprising the following processes:
[0097] Step (1), taking 2,4-dihydroxybenzophenone and 2M sodium hydroxide aqueous solution, mixing, stirring and dissolving, adding epichlorohydrin under nitrogen atmosphere, heating to 90°C for 4h; washing with water at 80°C, taking the organic phase and drying it, filtering, distilling under reduced pressure, recrystallizing it from ethanol, and vacuum drying to obtain epoxybenzophenone; the molar ratio of 2,4-dihydroxybenzophenone to epichlorohydrin is 1:2.5; the ratio of 2,4-dihydroxybenzophenone to sodium hydroxide aqueous solution is 0.2mol / 100mL;
[0098] Mix epoxy benzophenone and 30 wt% potassium hydroxide aqueous solution, heat to 80°C, and react for 10 hours; add dichloromethane, separate the liquids, take the organic phase, wash with water, dry, distill under reduced pressure, and dry in vacuum to obtain benzophenone diol; the ratio of epoxy benzophenone to potassium hydroxide aqueous solution is 30 g / 10 mL;
[0099] Under nitrogen atmosphere, 10 parts of benzophenone diol, 16.6 parts of bisphenol A epoxy diacrylate and 0.8 parts of tetrabutylammonium bromide were mixed, stirred and heated to 80°C, and kept warm for 24 hours; cooled to room temperature, tetrahydrofuran was added to dissolve, deionized water was added to separate the layers, rotary evaporated, and vacuum dried to obtain a modified epoxy resin;
[0100] Step (2), 100 parts of polypropylene, 10 parts of maleic anhydride grafted polypropylene, 6 parts of talc, 10 parts of calcium carbonate, 4 parts of glass fiber, 0.5 parts of coupling agent, 5 parts of epoxy resin (the mass ratio of bisphenol A epoxy resin and modified epoxy resin is 2:1), 0.1 parts of curing agent and 0.5 parts of antioxidant are mixed (temperature 100°C, time length 30min), extruded (temperature 190°C, screw speed 180rpm), pulled and stretched to form a panel and a core layer respectively, and compounded (temperature 190°C, pressure 0.35MPa) to obtain a polypropylene hollow plastic plate.
[0101] Comparative Example 3: A method for preparing a high-strength polypropylene hollow plastic plate, comprising the following processes:
[0102] Step (2), 85-100 parts of polypropylene, 10-15 parts of maleic anhydride grafted polypropylene, 6-8 parts of talc, 10-15 parts of calcium carbonate, 4-7 parts of glass fiber, 0.5-1.0 part of a coupling agent, 5-25 parts of an epoxy resin (the mass ratio of bisphenol A epoxy resin to novolac epoxy resin is 2:1), 0.1-5.0 parts of a curing agent and 0.5-1.0 part of an antioxidant are mixed (temperature 100°C, time length 30min), extruded (temperature 190°C, screw speed 180rpm), pulled and stretched to form a panel and a core layer respectively, and compounded (temperature 190°C, pressure 0.35MPa) to obtain a polypropylene hollow plastic plate.
[0103] Comparative Example 4: A method for preparing a polypropylene board, comprising the following processes:
[0104] 100 parts of polypropylene, 10 parts of maleic anhydride grafted polypropylene, 6 parts of talc (BHS-1250A, sourced from Quanzhou Xufeng Powder Raw Material Co., Ltd.), 10 parts of calcium carbonate, 0.5 parts of coupling agent and 0.5 parts of antioxidant were mixed (temperature 100°C, time 30 min), extruded (temperature 190°C, screw speed 180 rpm), pulled and stretched to form a panel and a core layer respectively, and compounded (temperature 190°C, pressure 0.35 MPa) to obtain a polypropylene hollow plastic board.
[0105] Experiment: Take the polypropylene hollow plastic plates obtained in Examples 1-3 and Comparative Examples 1-4 to prepare samples, test their properties and record the test results:
[0106] Flat compression performance test: Based on GB / T 1453 as the reference standard, an electronic universal material testing machine was used to test the static compression performance of the sample at a loading rate of 1 mm / min. Before the experiment, the sample was placed at 23°C and 50% RH for 24 hours.
[0107] Bending performance test: GB / T 1456 is used as the reference standard to test the bending performance of the sample at a loading rate of 2 mm / min;
[0108] UV resistance test: Place the sample under UV light for 28 days, including 8 hours of standard irradiation and 4 hours of standard condensation, and a cycle of 12 hours. Then test its bending performance again and calculate its bending strength retention rate;
[0109] Thermal stability test: Place the sample at 60°C for 3 hours, measure its dimensional change rate, and test the dimensional stability of the sample.
[0110] Flat compressive strength (MPa) Flexural strength (MPa) UV aging retention rate (%) Dimensional change rate (%) Example 1 3.5 21.3 101.9 0.04 Example 2 3.7 22.4 103.0 0.03 Example 3 4.0 23.7 104.5 0.01 Comparative Example 1 3.3 19.8 95.1 0.12 Comparative Example 2 2.9 17.2 100.4 0.15 Comparative Example 3 3.2 18.5 93.8 0.20 Comparative Example 4 1.5 10.5 88.2 0.32
[0111] According to the data in the above table, we can clearly draw the following conclusions:
[0112] The polypropylene hollow plastic plates obtained in Examples 1-3 were compared with those obtained in Comparative Examples 1-4. The test results show that:
[0113] Compared with the comparative example, the polypropylene hollow plastic plates obtained in Examples 1-3 have higher flat compressive strength, flexural strength and UV resistance retention rate data, which fully demonstrates that the present invention achieves improvements in the mechanical strength and UV resistance of the polypropylene hollow plastic plates.
[0114] Compared to Example 1, Comparative Example 1 replaced benzophenone diol with 1,5-pentanediol; Comparative Example 2 replaced bismaleimide glycidyl ether with bisphenol A epoxy diacrylate; Comparative Example 3 replaced the branched epoxy resin with a novolac epoxy resin; and Comparative Example 4 did not include the added epoxy resin component. Compared to Example 1, the polypropylene hollow plastic sheets obtained in Comparative Examples 1-4 showed decreased flat compressive strength, flexural strength, and UV resistance retention. This indicates that the present invention's design of the polypropylene hollow plastic sheet components and process improves their mechanical strength and UV resistance.
[0115] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "include," "comprise," or any other variations thereof are intended to encompass non-exclusive inclusion, such that a process, method, article, or apparatus comprising a series of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.
[0116] Finally, it should be noted that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art will be able to modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modifications, equivalent replacements, and improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.
Claims
1. A method for preparing a high-strength polypropylene hollow plastic plate, characterized in that: Including the following processes: Polypropylene, maleic anhydride grafted polypropylene, filler, epoxy resin, curing agent and additives are mixed, extruded, pulled and formed into panels and core layers respectively; the panel and the core layer are compounded to obtain a polypropylene hollow plastic plate.
2. The method for preparing a high-strength polypropylene hollow plastic plate according to claim 1, characterized in that: The epoxy resin is a mixture of one or more of branched epoxy resin, bisphenol A epoxy resin, bisphenol F epoxy resin and phenolic epoxy resin.
3. The method for preparing a high-strength polypropylene hollow plastic plate according to claim 2, characterized in that: The branched epoxy resin is prepared by the following process: Under the protection of nitrogen atmosphere, benzophenone diol, bismaleimide glycidyl ether and tetrabutylammonium bromide were mixed, stirred and heated to 80-90° C., and kept warm for 24 hours to obtain branched epoxy resin.
4. The method for preparing a high-strength polypropylene hollow plastic plate according to claim 3, characterized in that: The benzophenone diol is prepared by the following process: Take 2,4-dihydroxybenzophenone and sodium hydroxide aqueous solution, mix them, stir and dissolve them, add epichlorohydrin under the protection of nitrogen atmosphere, raise the temperature to 90-95°C and react for 3-4h to obtain epoxybenzophenone; Mix epoxy benzophenone and potassium hydroxide aqueous solution, heat to 80-85° C., and react for 9-10 hours to obtain benzophenone diol.
5. The method for preparing a high-strength polypropylene hollow plastic plate according to claim 3, characterized in that: The bismaleimide glycidyl ether is prepared by the following process: Mix bismaleimide, trimethylolpropane tris(3-mercaptopropionate) and a catalyst in chloroform, raise the temperature to 58-62° C. under nitrogen atmosphere protection, and stir to react for 100-150 minutes to obtain bismaleimide mercaptopropionate; Maleimide mercaptopropionate, allyl glycidyl ether and a photoinitiator are mixed in chloroform and subjected to ultraviolet irradiation for 4 to 5 hours to obtain bismaleimide glycidyl ether.
6. The method for preparing a high-strength polypropylene hollow plastic plate according to claim 1, characterized in that: The polypropylene hollow plastic plate comprises the following components: by mass, 85-100 parts of polypropylene, 10-15 parts of maleic anhydride grafted polypropylene, 20-30 parts of filler, 5-25 parts of epoxy resin, 0.1-5.0 parts of curing agent, and 1.0-2.0 parts of auxiliary agent.
7. The method for preparing a high-strength polypropylene hollow plastic plate according to claim 6, characterized in that: The filler comprises 6 to 8 parts of talc powder, 10 to 15 parts of calcium carbonate and 4 to 7 parts of glass fiber.
8. The method for preparing a high-strength polypropylene hollow plastic plate according to claim 3, characterized in that: The branched epoxy resin is prepared from the following components by mass: 10 parts of benzophenone diol, 54-61 parts of bismaleimide glycidyl ether and 0.8-1.0 parts of tetrabutylammonium bromide.
9. The method for preparing a high-strength polypropylene hollow plastic plate according to claim 1, characterized in that: The polypropylene hollow plastic plate comprises 2 to 3 groups of face panels, and a core layer is arranged between two adjacent groups of face panels; the thickness of the polypropylene hollow plastic plate is 4 to 15 mm; the thickness of the face panel is 1 to 5 mm, and the thickness of the core layer is 2 to 10 mm.
10. A high-strength polypropylene hollow plastic plate prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing composite talcum powder filled material of polypropylene
CN101092497A
High temperature-resisting hyperbranched epoxy resin and preparation method thereof
CN109320688A
Polypropylene composition and preparation method thereof
CN114409999A
Manufacturing method of fiber reinforced polypropylene composite material, and fiber reinforced polypropylene composite material
JP2020050801A
Interactive casing for a cosmetic product, in particular for make-up
KR1020190103058A